Exploring Health Information Technology Innovativeness and its Antecedents in Canadian Hospitals - Paré, G.; Jaana, M.; Sicotte, C. (Methods of Information in Medicine, 2010)
Objectives: The primary aim of this study was to assess the antecedents of health information technology (HIT) innovativeness in public hospitals. To do so, we built upon our own previous work to relate the level of HIT innovativeness to organizational capacity characteristics.Methods: We conducted a survey of chief information officers (CIOs) in public hospitals in the two largest Canadian provinces to identify the level of HIT innovativeness in these settings and test nine research hypotheses derived from the proposed research model. Results: A total of 106 completed questionnaires were received, which represents a response rate of 52%. Our findings indicate strong support for the research model. Seven out of nine hypotheses were supported indicating a significant relationship between HIT innovativeness and structural, financial, leadership, and knowledge sharing capacity characteristics. Results also reveal a moderate level of HIT innovativeness in the surveyed hospitals, with more emphasis on administrative systems and their integration than on clinical systems and emerging technologies.Conclusions: This study demonstrates that organizational characteristics are related to HIT innovativeness; this relationship holds irrespective of the public or private nature of hospitals.
Keywords: Health information technology; innovativeness; hospitals; organizational characteristics; survey